The Present Position of the Theory of International Trade - Gilbert, J. C. (Review of Economic Studies, 1935)
Journal Article The Present Position of the Theory of International Trade Get access J. C. Gilbert J. C. Gilbert Dundee Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 1, October 1935, Pages 18–34, https://doi.org/10.2307/2967568 Published: 01 October 1935